Patient-reported outcomes feedback report for knee arthroplasty patients should present selective information in a simple design - findings of a qualitative study - Kathrin I. Fischer; Diarmuid De Faoite; Matthias Rose (SpringerOpen, 2020)
Abstract Background Technical innovation to assess patient-reported outcomes (PROs) facilitates their implementation in clinical practice. In particular, mobile applications (apps) allow PROs to be assessed outside of the clinical setting. A patient's health status can be remotely monitored and evaluated after discharge, and their recovery process tracked. This is of particular interest for patients after knee arthroplasty, as the recovery phase after surgery usually takes place in an outpatient setting and requires a high level of patient engagement. Providing results of PRO assessments to patients in the form of a feedback report could increase patient engagement and may improve communication between health care professionals and patients. The aim of the study is to develop a PRO feedback report for mobile devices that is comprehensible and provides valuable information for patients after knee arthroplasty. Results In an iterative development process, our expert group developed two preliminary feedback reports (a text-based version and a graphical display) based on previous research results and practical experience. In a second step, we discussed these reports with orthopedic patients (n = 8) in terms of comprehensibility and value using semi-structured interviews and cognitive debriefing methods. Participants assessed the reports as informative, but had some difficulties in fully comprehending all of the information provided. Based on the feedback from patients, we modified both versions and reduced complexity to increase comprehensibility. Conclusions A PRO feedback report for patients for mobile app use has to take account of the heterogeneous user group, particularly demographics such as age and experience with mobile devices. Information should be presented in a simple way to be comprehensible and of value to patients. Technological advancements allow a simple default report to be set, something which enables patients interested in additional information to make customizations.